Coconut water as a resuscitation fluid and their effect on colon anastomosis healing in rats with hemorrhagic shock - Felipe, Jéssica Carvalho; Nascimento, Luciana Alves Tomaz do; Souza, Gabriela Silva Solino de; Toledo, Larissa Nogueira de; Medeiros, Vítor Brasil; Azevedo, Ítalo Medeiros; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2015)
Background/purpose: The hemorrhage and shock are important predictors of mortality and a serious complication particularly found in the perioperative colorectal surgery. Currently, there is no ideal fluid for volume replacement in shock. Relevant knowledge on the composition of coconut water (CW) is available, but studies on its use for resuscitation in shock are scarce. The aim of this study is to examine the influence of CW as a resuscitation fluid on the healing of colonic anastomosis in a model of hemorrhagic shock induced in rats. Methods: We used three groups of Wistar rats (6 each), weighing 251±18g. In group 1, rats were shocked and treated with Ringer lactate (RL); in Group 2, shocked rats were treated with modified CW (3% Na); Group 3 rats were not shocked and untreated (control). Results: The average rupture pressures of anastomoses were higher in the group submitted to hemorrhagic shock and treated with CW (190.5±7.5 mmHg) than in rats subjected to shock and treated with RL (159.2±6.6 mmHg). This difference was significant (p<0.05); in the control group the rupture pressure was 186.8±5.6mmHg. Comparing with the group treated with CW, the difference was not significant (p>0.05). Histopathological analysis showed better healing wounds in the group treated with CW, although the differences were not statistically significant comparing with the other groups. Conclusion: The data from this study showed that the volume replacement with CW with 3% sodium influenced positively the healing of colonic anastomoses in rats submitted to hemorrhagic shock model.